Life Long Learning: the Important and Future Change in Education - Mohd Bohari, Normila; Hatib Musta’amal, Aede; Mohamad, Norliza; Aisyah Che Derasid, Nur; Ahmad, Khalidah; Bahiyah Abdul Wahab, Nur (International Journal of Psychosocial Rehabilitation, 2020)
Education has a massive impact on the opportunities humans have to acquire and sustain the quality of life in the future. The transformation of education in Malaysia now requires a revolution in the pursuit of more flexible and continuous forms of knowledge. Lifelong learning is an approach to provide and produce excellent educational opportunities for everyone. The importance of lifelong learning is that it is one of the mediums to provide a continuous education path. Malaysia's transformation by empowering lifelong learning in the Malaysia Education Blueprint 2015-2025 is one of the best measures to bring about significant changes in the knowledge-based economy as well as in the Industrial Revolution (IR 4.0) of education. Hence, this systematic literature review presents the discussion of the research questions, which are related to the importance and challenges of lifelong learning for teachers. PRISMA is a methodology used to determine the research journals that have empirical data in their systematic literature review and are appropriate for the study. In the findings, 15 journals have been identified as relevant materials for this research, and the themes are teachers’ competency, professional development, students' needs, curriculum change, technologies, and social support. Due to these reasons, lifelong learning is to be more relevant to the changing globalization of today's world that focuses on aspects of the skills and the development of information technology. The future recommendation focuses on the approaches to relate with skill in lifelong learning to prepare a holistic teacher for human capital.